Analisis Indeks Kepuasan Masyarakat pada Kantor Kelurahan Malanu Kota Sorong - Fera A Sabir; Meyta Longkutoy; Agnes Eyne Banea (Departement of Mathematics Education, 2023)
This study aims to determine the community satisfaction index in the Malanu Village referring to KEMENPAN Number 14 of 2017 concerning Guidelines for Compiling a Community Satisfaction Survey. The research method used is a quantitative descriptive method, referring to the community satisfaction survey method. The community satisfaction index is based on the assessment element, so the results of community service are obtained, namely not good, not good, good and very good. The interval 88.31 - 100.00 obtains a very good service quality value, obtained from the elements of the system, mechanism and procedure (U1), has a conversion value of 89.3. The interval 76.71 – 88.30 obtains a good service quality score, obtained from the requirements element (U2), has a conversion value of 87.5; while the interval 65.00 - 76.60 obtained a poor service quality score obtained from the elements of completion time (U3), costs/tariffs (U4), implementing competence (U6) and infrastructure (U9), followed by intervals 25.00 - 64.99 obtaining a service quality value that is not good is obtained from product elements, service specifications, implementing behavior, handling complaints, suggestions and input. Overall, the performance of service units in the Malanu Sub-District includes poor service quality.